The Implementation of Electronic Speed Control on Electric Scooter for Optimum Performance - Maslan, Nur Amal Aqilah (2017)
Electric scooter has been one of the favorable vehicles for the users’ in previous years and it is not too much to mention that the electric scooter has its own fans. The electric scooter is a vehicle that is powered by electricity and drives by the motor. However, due to the problems that the users encounter upon using the electric scooter such as low speed, the electric scooter has seem to not be favorable as it was, years ago. The Electronic Speed Control (ESC) is implemented to the existing prototype to control the speed. In the system, the ESC takes place to control the speed of the DC motor as well as the direction of rotation of the motor. The methods on the speed control of the electric scooter and the selection of gears are explained in this paper. The research, reading, and review on the types of motor, the types of ESC and the gears performance are done to verify and identify the best items for the accuracy and the optimum performance of the system. The implementation of the ESC to the system is being conducted as well and the performance of the ESC to the system is being observed.